2022
DOI: 10.3390/molecules27207126
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Identification of New N,N-Disubstituted Thiourea, and Thiazolidinone Scaffolds Based on Quinolone Moiety as Urease Inhibitor

Abstract: Synthesis of thiazolidinone based on quinolone moiety was established starting from 4-hydroxyquinol-2-ones. The strategy started with the reaction of ethyl bromoacetate with 4-hydroxyquinoline to give the corresponding ethyl oxoquinolinyl acetates, which reacted with hydrazine hydrate to afford the hydrazide derivatives. Subsequently, hydrazides reacted with isothiocyanate derivatives to give the corresponding N,N-disubstituted thioureas. Finally, on subjecting the N,N-disubstituted thioureas with dialkyl acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The human mammary gland epithelial (MCF-10A) normal cell line was used to investigate the viability effect of new targets 9a–g on viability. 46,47 Refer to Appendix A for more details.…”
Section: Methodsmentioning
confidence: 99%
“…The human mammary gland epithelial (MCF-10A) normal cell line was used to investigate the viability effect of new targets 9a–g on viability. 46,47 Refer to Appendix A for more details.…”
Section: Methodsmentioning
confidence: 99%
“…Elshaier et al [83] . synthesized quinolone based derivatives of thiazolidinone 8 and tested them for their in vitro antiurease activity ( Canavalia ensiformis ).…”
Section: Thiazolidinones As Urease Inhibitorsmentioning
confidence: 99%
“…Elshaier et al [83] synthesized quinolone based derivatives of thiazolidinone 8 and tested them for their in vitro antiurease activity (Canavalia ensiformis). Results found that the tested compounds exhibited moderate urease inhibitory potential (IC 50 = 18.80-45.43 μM).…”
Section: Thiazolidinones As Urease Inhibitorsmentioning
confidence: 99%
“…They have reported to act as inhibitors of DNA gyrase, topoisomerase, and as urease inhibitors. 2,28,31 1.1. Rational of the Design.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds incorporating quinoline-based bioactive heterocycles such as pyrrole, pyrazoline, or benzopyrrole rings have drawn considerable attention with pronounced antimicrobial effect. These compounds were utilized as broad spectrum antibiotic drugs that work on both Gram-positive and Gram-negative pathogens as well as many fungal strains. The antimicrobial effect of these classes of compounds is mediated through different mechanisms. They have reported to act as inhibitors of DNA gyrase, topoisomerase, and as urease inhibitors. ,, …”
Section: Introductionmentioning
confidence: 99%